2015
DOI: 10.1007/s10552-014-0498-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of TGF-β2 levels in breast milk with severity of breast biopsy diagnosis

Abstract: Purpose TGF-β plays a dual role in breast carcinogenesis, acting at early stages as tumor-suppressors and later as tumor-promoters. TGF-β isoforms are expressed in breast tissues and secreted in milk, suggesting that analysis of levels in milk might be informative for breast cancer risk. Accordingly, we assessed TGF-β2 levels in milk from women who had undergone a breast biopsy and related the concentrations to diagnosis. Methods Milk donated by women who had undergone or were scheduled for a breast biopsy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…106,109111 Yang et al said the expression of TGF-β in the breast milk increased the risk of BC. 112 van’t Veer et al claimed that CD24 was abundant in patients with late-stage BC, 113 and Wang et al demonstrated CD82 expression level was negatively associated with patients with BC. 114 As for miRNA, miR-10b and miR-145 are abundant in patients with BC.…”
Section: Cancer Clinical Applications Of Evmentioning
confidence: 99%
“…106,109111 Yang et al said the expression of TGF-β in the breast milk increased the risk of BC. 112 van’t Veer et al claimed that CD24 was abundant in patients with late-stage BC, 113 and Wang et al demonstrated CD82 expression level was negatively associated with patients with BC. 114 As for miRNA, miR-10b and miR-145 are abundant in patients with BC.…”
Section: Cancer Clinical Applications Of Evmentioning
confidence: 99%
“…As reviewed previously, a non‐invasive tool for early detection of BC could be particularly beneficial for women of reproductive age, as current imaging tools are less effective in detecting cancer in the relatively dense breasts of younger women, and because the incidence of pregnancy associated BC is predicted to increase as the age of first pregnancy increase. Empirical studies support the use of human milk to investigate potential BC biomarkers . Dysregulated proteins in breast milk could provide potential biomarkers of BC.…”
Section: Introductionmentioning
confidence: 99%
“…Human breast milk has been proposed as a suitable bodily fluid for discovering biomarkers useful in early detection of BC, as well as for assessing future risk . Breast milk contains secreted proteins, immune cells and exfoliated epithelial cells originating throughout the organ.…”
Section: Introductionmentioning
confidence: 99%